2002
DOI: 10.1063/1.1459487
|View full text |Cite
|
Sign up to set email alerts
|

GaN tunnel junction as a current aperture in a blue surface-emitting light-emitting diode

Abstract: We have demonstrated surface-emitting GaN-based diodes with a buried tunnel junction (TJ) current aperture. The current confinement aperture for lateral injection current was defined by mesa etch of a TJ structure and regrowth of current blocking layer surrounding the TJ mesa. Lateral electron current drives a tunnel contact junction providing hole injection into the active region. The very uniform light emission just through a buried TJ aperture represents that the buried TJ structure acts very effectively as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Details of the MOCVD growth procedures have already been published elsewhere [9]- [13]. Briefly, the LED structure consists a 30-nm-thick low-temperature GaN nucleation layer, a 2-m-thick Si-doped n-GaN buffer layer, an InGaN-GaN MQW active region, a 50-nm-thick Mg-doped p Al Ga N cladding layer, a 0.25-m-thick Mg-doped p-GaN layer and an Si-doped n -SPS tunnel contact structure [14]. The undoped InGaN-GaN MQW active region consists 5 periods of 3 nm-thick In Ga N well layers and 7-nm-thick GaN barrier layers.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the MOCVD growth procedures have already been published elsewhere [9]- [13]. Briefly, the LED structure consists a 30-nm-thick low-temperature GaN nucleation layer, a 2-m-thick Si-doped n-GaN buffer layer, an InGaN-GaN MQW active region, a 50-nm-thick Mg-doped p Al Ga N cladding layer, a 0.25-m-thick Mg-doped p-GaN layer and an Si-doped n -SPS tunnel contact structure [14]. The undoped InGaN-GaN MQW active region consists 5 periods of 3 nm-thick In Ga N well layers and 7-nm-thick GaN barrier layers.…”
Section: Methodsmentioning
confidence: 99%
“…10) GaN TJs grown by metalorganic chemical vapor deposition (MOCVD) have been explored since 2001 but have faced issues of large voltage penalties of 1.0 to 3.2 V and low light output power. [11][12][13] One problem with MOCVD-grown TJs is the magnesium memory effect. 14) Excess magnesium lingering in the reactor may diffuse into n-GaN layers and compensate for silicon, reducing the concentration of donors available.…”
mentioning
confidence: 99%
“…Initial studies on TJ contacts with p-GaN were reported by several research groups. [1][2][3][4][5] However, the interband tunneling process was inefficient, and the devices showed a high turn-on voltage and on-resistance, precluding wide-spread adoption of TJs in optoelectronic devices. After low-resistance polarization-engineered n-GaN=InGaN= p-GaN junctions grown by plasma-assisted molecular beam epitaxy (PA-MBE) were demonstrated, efforts to utilize polarization-assisted high electric fields to enhance the tunneling process by reducing the tunneling width and barrier for the carriers rekindled interest in wide-band-gap TJs.…”
mentioning
confidence: 99%